Contraction of a shear-thinning axisymmetric cavity - Lu, Jiakai (2019)
We investigate the capillary driven collapse of a small contracting cavity or hole in a shear-thinning fluid. We find that shear-thinning effects accelerate the collapse of the cavity by decreasing the apparent liquid viscosity near the cavity's moving front. Scaling arguments are used to derive a power-law relationship between the size of the cavity and the rate of collapse. The scaling predictions are then corroborated and fully characterized using high-fidelity simulations. The new findings have implications for natural and technological systems including neck collapse during microbubble pinch-off, the integrity of perforated films and biological membranes, the stability of bubbles and foams in the food industry, and the fabrication of nanopore based biosensors.